Atividade de morcegos insetívoros (mammalia, chiroptera) no pampa brasileiro: uso de hábitat e sazonalidade - Barros, Marília Abero Sá de (2012)
Bats correspond to 20% of the extant mammal species and, with a few exceptions, use echolocation, a spacial orientation system based on emission and analysis of echoes from sound waves, generally ultrasounds. Echolocation was discovered in the 1940 s and since the 1970 s ultrasound detectors have been commercially available, allowing the investigation of several aspects of the natural history and ecology of bats. Passive acoustic monitoring has been frequently used in habitat use studies, predominantly in North America and Europe, by comparing the number of bat passes between different habitat types. This dissertation presents the first evaluation of the spacial and seasonal variation patterns in the activity of insectivorous bats in the Brazilian biome Pampa, in the state of Rio Grande do Sul. Since bat activity can vary according to habitat type, time of year and climatic conditions, the following hypotheses were tested: 1. bat activity varies between different types of habitat; 2. bat activity varies seasonally; 3. bat activity is influenced by temperature, humidity and wind speed. The acoustic samples were taken along fixed transects of 1500 meters, which were monitored monthly from April 2009 to March 2010. Five habitat types were sampled: eucalypts, stream, riparian forest, wetland and grassland. In each sample, the number of bat passes was obtained by using an ultrasound detector Pettersson D230. A total of 1183 bat passes were registered. Greater bat activity levels was observed along large eucalypts (1.93 bat passes/3min) and along a stream (1.61 bat passes/3 min). A riparian forest (0.94 bat passes/3 min) and a wetland area (0.61 bat passes/3 min) exhibited statistically equal levels of activity. Bat passes were fewer in grassland areas (0,16 bat passes/3 min). Bat activity was not correlated with abiotic factors. However, bat activity was significantly low in the colder season, winter, and was similar in autumn, spring and summer. The observed preference for vegetation borders and water courses agrees with reports from other countries and is attributed predominantly to the high prey abundance in these types of environments. Additionally, low activity in the winter is probably a response to the reduced availability of insects, and to lower temperatures. Our results indicate which areas of arboreal vegetation and water courses should be priorities for the conservation of bats and that alterations of these habitat types might negatively influence bat activity in the region